Rice Cultivation Systems in Latin America: Diversity and Climate Vulnerability - Suárez, Ronny (Journal of Environmental Management and Tourism; Vol 17 No 2 (2026): JEMT, Volume XVII, Issue 2(82), Summer 2026DO - 10.14505/jemt.v17.2(82).02, 2026)
Rice cultivation systems in Latin America exhibit substantial heterogeneity driven by geographic, climatic, technological, and institutional factors. These differences shape productivity outcomes, exposure to climate risks, greenhouse gas emissions, and producers’ adaptive capacity. This article provides a system-oriented analysis of the main rice production systems in the region, distinguishing among irrigated, partially irrigated, and rainfed systems, as well as mechanized, semi-mechanized, and traditional (no mechanized) production models. It examines how water management, mechanization, cropping intensity, and socioeconomic conditions interact to influence climate vulnerability and the feasibility of adaptation and mitigation strategies. The analysis highlights the importance of differentiated system-sensitive climate-smart agriculture pathways aligned with local production contexts and producer realities across Latin America.